Evolutionary models of antibody lineages - Hoehn, K (2017)
Antibodies are proteins released into the blood and mucosa to identify and neutralize invading pathogens by binding to structures on their surface (antigens). Before being exported as antibodies, these vital components of the adaptive immune system are expressed, and refined, as membrane-bound B cell receptors (BCRs). BCRs are initially formed through somatic recombination of germline DNA, creating a large repertoire of unique sequences. After encountering antigen for the first time, BCRs undergo an evolutionary process of somatic mutation and clonal selection leading to improved antigen binding. Recently, next-generation sequencing has provided an unprecedented ability to characterize the genetic diversity of BCRs within individuals. Chapter 1 of this thesis overviews the work done elsewhere in the field until now. Chapter 2 uses summary statistics applied to high-throughput sequence data from a clinical trial to explore the genetic changes that occur in the repertoire during HIV infection. The results of these analyses motivated a more rigorous, model-based approach to understanding BCR diversity. Chapter 3 introduces a new phylogenetic substitution model that relaxes common model assumptions that are violated by somatic hypermutation. Chapter 4 expands this model to incorporate previously defined empirical models of somatic hypermutation, providing a more complete model of B cell maturation. Chapter 5 uses the models developed in Chapters 4 and 5 to explore dynamics of clonal selection during the maturation of three HIV broadly neutralizing antibody lineages. Finally, Chapter 6 shows how this framework may be scaled up to characterize data from entire BCR repertoires from a phylogenetic perspective.